2022
DOI: 10.3389/fvets.2022.1004841
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid reduced apparent protein digestibility and induced oxidative stress and inflammatory response without altering growth performance and ruminal microbiota diversity of Xiangdong black goats

Abstract: The present study was performed to evaluate the impacts of tannic acid (TA) supplementation at different levels on the growth performance, physiological, oxidative and immunological metrics, and ruminal microflora of Xiangdong black goats. Twenty-four goats were randomly assigned to four dietary treatments: the control (CON, basal diet), the low-dose TA group [TAL, 0.3 % of dry matter (DM)], the mid-dose TA group (TAM, 0.6 % of DM), and the high-dose TA group (TAH, 0.9 % of DM). Results showed that the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…In the rumen liquid obtained from the RUSITEC system of this trial, the bacterial community at the phylum level was successively dominated by Proteobacteria, Bacteroidota, and Firmicutes, which further confirmed the predominance of these three bacterial phyla in the ruminal microbiome reported in precedent investigations including our prior studies ( Rey et al, 2014 ; Wang et al, 2017a , 2020 , 2021 , 2022 ; Zhong et al, 2018 ). Besides, the genera Rikenellaceae_RC9_gut_group , Succinivibrionaceae_UCG_002 , and Ruminobacter , and the species Ruminobacter amylophilus were, respectively, identified as the prominent ruminal bacterial taxa in this experiment, and this result was also supported by the findings of previous researches ( Cui et al, 2021 ; Daghio et al, 2021 ; Wu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the rumen liquid obtained from the RUSITEC system of this trial, the bacterial community at the phylum level was successively dominated by Proteobacteria, Bacteroidota, and Firmicutes, which further confirmed the predominance of these three bacterial phyla in the ruminal microbiome reported in precedent investigations including our prior studies ( Rey et al, 2014 ; Wang et al, 2017a , 2020 , 2021 , 2022 ; Zhong et al, 2018 ). Besides, the genera Rikenellaceae_RC9_gut_group , Succinivibrionaceae_UCG_002 , and Ruminobacter , and the species Ruminobacter amylophilus were, respectively, identified as the prominent ruminal bacterial taxa in this experiment, and this result was also supported by the findings of previous researches ( Cui et al, 2021 ; Daghio et al, 2021 ; Wu et al, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
“…In the rumen liquid obtained from the RUSITEC system of this trial, the bacterial community at the phylum level was successively dominated by Proteobacteria, Bacteroidota, and Firmicutes, which further confirmed the predominance of these three bacterial phyla in the ruminal microbiome reported in precedent investigations including our prior studies (Rey et al, 2014;Wang et al, 2017aWang et al, , 2020Wang et al, , 2021Wang et al, , 2022Zhong et al, 2018). Besides, the genera Rikenellaceae_ RC9_gut_group, Succinivibrionaceae_UCG_002, and Ruminobacter,…”
Section: Discussionsupporting
confidence: 87%
“…The ruminal microbiota plays a crucial function in promoting nutrient digestion and utilization, which are closely associated with growth performance and production efficiency [31]. A previous study demonstrated that several species from Prevotella play an important role in protein fermentation [32]. Thus, we further investigated the influence of SIFs on ruminal microbiota using 16S rRNA gene sequencing technology.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the reduction in fiber digestibility could be explained by the high polyphenols content especially tannin, which may bind the bacterial enzymes, prevent the microbial attachment to dietary fibers, or form complexes with cellulose, hemicellulose and pectin (Frutos et al, 2004 ). Furthermore, it was indicated that although high tannin content in feeds that bind with protein can increase the amount of rumen undegradable protein, it may also restrain the synthesis of microbial protein in rumen (Wang et al, 2022 ). Wanapat et al ( 2008 ); Odhaib et al 2018a ); Kholif et al ( 2021 ) suggested that the reducing effect of the medicinal plant’s mixture on digestibility compared with the sole supplement may be ascribed to a synergistic effect or a dose-dependent of these supplements.…”
Section: Discussionmentioning
confidence: 99%